An Internet of Things (IoT) Based Neighbourhood Distress Alert System - Ahiara, Wilson Chukwuemeka; Chukwugoziem IHEKWEABA (ABUAD Journal of Engineering Research and Development (AJERD), 2023)
To acquiesce to the increase in territorial invasion of communities by hoodlums, bandits and kidnappers every day, some communities have resorted to engage the services of security agents or guards to watch over and alert them in the case of any security breach. However, the neighbourhood s found in some locations especially, in the rural areas impact on the cost of employing guards, and the consequent disagreement amongst residents in the neighbourhood security meeting. This paper proposes an Internet of Things (IoT) based system for alerting residents in a neighbourhood as well as reporting the actual location of a particular neighbour in distress. To achieve this, a hardware system based on NodeMCU with built-in Wi-Fi chip for internet routing is designed. Communication is established remotely between the hardware system and the cloud through the server Application Programming Interface (API) that utilizes cloud resources such as Short Message Service (SMS) gateway and Google map API to craft SMS and fetch location coordinate from Google map Uniform Resource Location (URL) respectively. This piece of information is then displayed on the Liquid Crystal Display (LCD) device on users’ machine and mobile phones in real time for notification. The test carried out shows that the developed system is reliable and affordable for use in a neighbourhood.